Large-Scale Applications of Amide Coupling Reagents for the Synthesis of Pharmaceuticals - Dunetz, Joshua R; Magano, Javier; Weisenburger, Gerald A (Organic process research & development, 2016)
This review showcases various coupling reagents which have been implemented specifically for large-scale amide synthesis via the condensation of an acid and amine, while highlighting the benefits and drawbacks of each reagent on an industrial scale.